Foam Rolling Intervention Improves Lactate Clearance After High-Intensity Exercise - Kazuki Kasahara; Keita Oneyama; Takeru Ito; Masatoshi Nakamura; Genta Ochi (Sports)
The acute effects of a foam rolling intervention on lactate clearance and the impaired executive function associated with fatigue after high-intensity exercise remain unclear. This study examined whether foam rolling is an effective tool for fatigue recovery. Eighteen healthy adults without consistent exercise habits participated in this study. Participants performed high-intensity exercises, and the post-exercise foam rolling intervention was compared to the control condition. Measurements included lactate, vigor/fatigue by the Profile of Mood States 2nd Edition, cognitive function (cognitive task performance), leg and body rating of perceived exertion pre- and post-exercise, and post-intervention. Blood lactate concentrations post-foam rolling intervention (−7.3 ± 3.0 mmol/L) were significantly reduced among all participants. Increased lactate clearance by foam rolling correlated with a faster recovery of executive function for those with greater lactate clearance. However, cognitive fatigue was not observed after high-intensity exercise (p = 0.086, r = 0.41). Lactate clearance was not significantly correlated with the rating of perceived exertion in the foam rolling condition. The rating of the perceived exertion decreased with increased lactate clearance for those with greater lactate clearance in the control condition (leg: r = 0.778; body: r = 0.669). In conclusion, foam rolling intervention may be effective for exhausting exercise recovery.